2
$\begingroup$

Let $N > 0$ be an integer. Suppose $Y$ is a random variable on $\Omega$ and define, for $n = 0, 1, \ldots, N$, $$ Y_n = \tilde{E}_n(Y) $$ (i.e. the conditional expectation with respect to the risk-neutral probability measure $\tilde{\mathbb{P}}$). Further, let $Z_0, Z_1, \ldots, Z_n$ be the Radon–Nikodym derivative process of $\tilde{\mathbb{P}}$ with respect to $\mathbb{P}$, so $Z_n = E_n(Z)$, with $Z$ the Radon–Nikodym derivative of $\tilde{\mathbb{P}}$ with respect to $\mathbb{P}$. Show that the process $$ Z_0 Y_0, Z_1 Y_1, \ldots, Z_N Y_N $$ is a martingale with respect to $\mathbb{P}.$

Since I am stuck on this for hours, any help would be greatly appreciated. I have no idea how to deal with the conditional expectation in the expression we have to show, which is $E_n(Y_{n+1} Z_{n+1}) = Y_n Z_n.$

$\endgroup$
  • $\begingroup$ It would help to define the "risk-neutral probability measure" since that is not apparent from context. $\endgroup$ – Math1000 May 25 '18 at 12:04
0
$\begingroup$

You want to show that $$E[1_AY_{n+1}Z_{n+1}] = E[1_AY_{n}Z_{n}]$$ for every $A \in \mathcal{F}_n$.

\begin{align} E[1_AY_{n+1}Z_{n+1}] &= E[1_AY_{n+1}E[Z\mid\mathcal{F}_{n+1}]]\\ &= E[E[1_AY_{n+1}Z\mid\mathcal{F}_{n+1}]]\\ &= E[1_AY_{n+1}Z]\\ &= \tilde{E}[1_AY_{n+1}]\\ &= \tilde{E}[1_AY_{n}]\\ &= E[1_AY_{n}Z]\\ \end{align}

On the other hand,

\begin{align} E[1_AY_{n}Z_{n}] &= E[1_AY_{n}E[Z\mid\mathcal{F}_{n}]]\\ &= E[E[1_AY_{n}Z\mid\mathcal{F}_{n}]]\\ &= E[1_AY_{n}Z]\\ \end{align}

Let me know if you don't see how I went from step to the other.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.